Internet television at the local level: Challenges in regulating online media. (1st September 2018) - Martori Muntsant, Aida
In a context of globalization of media landscape where big players provide content worldwide, broadcasters that cover topics related to local areas are still necessary. Due to the limitation of licenses in conventional television (such as digital terrestrial television), the denial of distribution platforms to local channels (as is the case of Movistar+ in Spain) and the aim of local channels to be in the digital sphere, one can find many local stations broadcasting online. The goal of this article is to point out the phenomenon of Internet television at the local level, and to explain the opportunity to regulate them like local television channels. The Catalan case, in Spain, will be presented as a paradigmatic example with a long tradition of local television, where more than twenty broadcasters turn to Internet due to the lack of entry barriers to online television market.